SISTEM INFORMASI PEMESANAN PRODUK CHEMICAL PADA PT. PAKARTI MAJU MANDIRI BERBSASIS WEB - Andira Yulianingrum (2022)
The development of the technological world that continues to evolve rapidly today in the field of information and communicationThe impact of the past two years has caused several companies to experience a decline in revenue. From this, many people open business opportunities by utilizing technology, one of which is online sales based on the existing conditions of PT. Pakarti Maju Mandiri opened a business by selling drugs (chemical) , PT. PMM also experienced the same conditions as other businesses, they experienced a decrease in income due to contact activities that had to be temporarily dismissed, causing the product marketing process to decrease. Progress is needed to restore the decline in product marketing, so a Chemical Product Order Information System was designed at PT. Pakarti Maju Mandiri Web-Based. The system can be used by online buyers and facilitates the transaction process between buyers and owners. The design of this Ordering Information System performs analysis with the waterfall method and design (Unified Modelling Language) UML, PHP and MYSQL programming languages for database purposes in the process. The expected result is that it can realize the management of an efficient ordering information system and help PT. Pakarti Maju Mandiri.